Pharmacokinetic Profile and Oral Bioavailability of Diosgenin, Charantin, and Hydroxychalcone From a Polyherbal Formulation - Salunkhe, Ruchira; Gadgoli, Chhaya; Naik, Archana; Patil, Nikita (Frontiers in Pharmacology, 2021)
Background: Diosgenin, Charantin, and Hydroxychalcone are utilized for standardization of popular antidiabetic herbal drugs Trigonella foenum-graecum L, Momordica charantia L, and Cinnamomum verum J. Presl respectively. However, no reports on bioavailability of these markers were available. The present study was undertaken to determine bioavailability and pharmacokinetic profile of the markers and formulations containing the herbs. Methods: The pharmacokinetic profile and absolute bioavailability of the pure active markers were determined in male Wistar rats by administering individually the doses of 1.5 mg/kg i. v. and 15 mg/kg p. o, followed by estimation of serum levels of the markers at 0, 10, 30, 60, 120, 240mins till 24hrs time points by a validated bioanalytical HPTLC method. Two standardized antidiabetic capsule formulations containing spray dried hydro alcoholic extracts of seeds of Trigonella foenum-graecum L. (42.8 mg equivalent to 0.95 %w/w of Diosgenin), fresh fruits of Momordica charantia L. (21.4 mg equivalent to 0.4% w/w of Charantin) and bark of Cinnamomum verum J. Presl (10.71 mg equivalent to 0.079 %w/w Hydroxychalcone), were prepared. In one formulation, piperine 1.5mg was added along with the other herbal extracts mentioned. Bioavailability and pharmacokinetic profile of these two formulations were determined in male Wistar rats through estimating serum levels of active markers Diosgenin, Charantin and Hydroxychalcone at 0, 10, 30, 60, 120, and 240mins till 24hrs later oral administration of the formulations (Formulation without Piperine F1 and Formulation with Piperine F2). Results: Plasma concentrations were found to decline mono exponentially following intravenous administration and the mean elimination half-life (t1/2) were observed to be 7.93, 8. 21, 4.66h respectively. The absolute oral bioavailability of pure markers was observed to be 9.0±0.2%, 8.18±0.36% and 10.54±0.52% by dose normalization method. The oral bioavailabilities of the formulations with respect to Diosgenin, Charantin and Hydroxychalcone were found to be 9.78, 10.743 and 8.07% respectively. The formulation containing piperine indicated significant (P< 0.01) increase in the bioavailabilities of all the marker compounds. Conclusion: In conclusion, the Diosgenin and Charantin have low bioavailability as compared to Hydroxychalcone. The bioavailabilities of all the three marker compounds can be increased exponentially with the addition of piperine.